2014
DOI: 10.1002/bem.21840
|View full text |Cite
|
Sign up to set email alerts
|

Maternal residential proximity to sources of extremely low frequency electromagnetic fields and adverse birth outcomes in a UK cohort

Abstract: Studies have suggested that exposure to extremely low frequency electromagnetic fields (ELF-EMF) may be associated with increased risk of adverse birth outcomes. This study tested the hypothesis that close proximity to residential ELF-EMF sources is associated with a reduction in birth weight and increased the risk of low birthweight (LBW), small for gestational age (SGA) and spontaneous preterm birth (SPTB). Closest residential proximity to high voltage cables, overhead power lines, substations or towers duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…This study is an important addition to research on the health affected by power lines. Only a few studies have investigated the pregnancy outcome affected by power lines, but the researchers showed that the electromagnetic field exposure of pregnant women did not increase the risk of pregnancy outcomes [19,[21][22][23]. In this investigation, we found that women who were living in less than 600 meters from high voltage power lines had higher spontaneous preterm birth and birth defects compared to those living farther than 600 meters.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This study is an important addition to research on the health affected by power lines. Only a few studies have investigated the pregnancy outcome affected by power lines, but the researchers showed that the electromagnetic field exposure of pregnant women did not increase the risk of pregnancy outcomes [19,[21][22][23]. In this investigation, we found that women who were living in less than 600 meters from high voltage power lines had higher spontaneous preterm birth and birth defects compared to those living farther than 600 meters.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, the results from some studies have indicated that exposure to magnetic field may be associated with the increased risk of adverse birth outcomes such as low birth weight [16] and miscarriages [17]. Some studies, however, did not find a statistically significant increased risk of preterm birth and low birth weight in relation to exposure to electromagnetic field during pregnancy [18,19] reproductive outcomes [14]. Pregnant women in Iran sometimes live very close to very high voltage overhead power lines and are exposed to electromagnetic fields [11].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent among these studies is the potential for temporal ambiguity as it is unclear if the exposure preceded the outcome. Using data from 140,356 births derived from England’s North West Perinatal Survey Unit database, de Vocht et al (2014) examined the potential relationships between residential proximity to nearest magnetic field source (potential sources included: high voltage cables, overhead power lines, or electricity substations or towers) and the following birth measures: preterm birth, spontaneous preterm birth (which excluded elective deliveries), small-for-gestational-age (defined as birth weight <10 th percentile), low birth weight, and birth weight. While no apparent associations were observed for 4 clinical birth outcomes, de Vocht et al (2014) found that there was a reduction in average birth weight for participants that lived in homes that were ≤50 m from a source (adjusted beta: −212 g, 95% CI: −395, −29 g).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…Using data from 140,356 births derived from England’s North West Perinatal Survey Unit database, de Vocht et al (2014) examined the potential relationships between residential proximity to nearest magnetic field source (potential sources included: high voltage cables, overhead power lines, or electricity substations or towers) and the following birth measures: preterm birth, spontaneous preterm birth (which excluded elective deliveries), small-for-gestational-age (defined as birth weight <10 th percentile), low birth weight, and birth weight. While no apparent associations were observed for 4 clinical birth outcomes, de Vocht et al (2014) found that there was a reduction in average birth weight for participants that lived in homes that were ≤50 m from a source (adjusted beta: −212 g, 95% CI: −395, −29 g). In a follow-up analysis, de Vocht and Lee (2014) re-analyzed the dataset using statistical measures to address missing data (multiple imputation) and residual confounding (propensity score matching), and again found that babies from mothers residing in homes ≤50 m from a source had a reduced birth weight (adjusted beta: −116 g, 95% CI: −224, −7 g).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…ELF-EMF has devastating effects on the reproductive system of female rats, e.g., it reduces the number of flushed blastocysts and increases the height of the epithelial cells in the fallopian tubes (9). ELF-EMF radiation can cause changes in the uterus and ovaries in rats (10), influence follicular development, influence the estrus cycle, and cause birth defects, miscarriage, and premature birth (11). The development of tissues, organs, and systems during embryogenesis is sensitive to toxic agents (10).…”
Section: Introductionmentioning
confidence: 99%